New Neurons in Aging Brains: Molecular Control by Small Non-Coding RNAs - Schouten, Marijn; Buijink, M R.; Lucassen, Paul J.; Fitzsimons, Carlos P. (Frontiers in Neuroscience, 2012)
Adult neurogenesis generates functional neurons from neural stem cells present in specific brain regions. It is largely confined to two main regions: the subventricular zone of the lateral ventricle, and the subgranular zone of the dentate gyrus (DG), in the hippocampus. With age, the function of the hippocampus and particularly the DG is impaired. For instance, adult neurogenesis is decreased with aging, in both proliferating and differentiation of newborn cells, while in parallel an age-associated decline in cognitive performance is often seen. Surprisingly, the synaptogenic potential of adult-born neurons is only marginally influenced by aging. Therefore, although proliferation, differentiation, and synaptogenesis of adult-born new neurons in the DG are closely related to each other, they are differentially affected by aging. In this review we discuss the crucial roles of a novel class of recently discovered modulators of gene expression, the small non-coding RNAs, in the regulation of adult neurogenesis. Multiple small non-coding RNAs are differentially expressed in the hippocampus. In particular a subgroup of the small non-coding RNAs, the microRNAs, fine-tune the progression of adult neurogenesis. This makes small non-coding RNAs appealing candidates to orchestrate the functional alterations in adult neurogenesis and cognition associated with aging. Finally, we summarize observations that link changes in circulating levels of steroid hormones with alterations in adult neurogenesis, cognitive decline, and vulnerability to psychopathology in advanced age, and discuss a potential interplay between steroid hormone receptors and microRNAs in cognitive decline in aging individuals.